Особливості виробничої складової економічної кризи на рівні держави та регіону - Кучінка, Т. В.; Kuchinka, T. V. (Видавництво Львівської політехніки, 2017)
Актуальність теми дослідження полягає у комплексному оцінюванні виробничої складової економічної кризи як невід’ємної частини механізму державного управління кризовими процесами. Значна увага приділяється визначенню величини індикаторів та їх характеристичних значень на рівні держави та Закарпатської області. У процесі дослідження використано загальнонаукові методи: аналізу, синтезу, побудови динамічних рядів; застосовано табличні та графічні методи. Наукова новизна дослідження полягає у визначенні рівня безпеки виробничої складової економічної кризи держави та регіону. Практична значущість полягає у можливості використання результатів дослідження для комплексної оцінки економічної кризи держави та регіону.

The article is devoted to the study of the economic crisis’ indicators and appropriateness of the choice of indicators of the economic cycle as indicators of the system of economic security of regions and countries. The topicality of the research consists in the integral estimation of the economic crisis’ production field, as an inherent part of state crisis management. Much attention has been paid to the definition of indicators and their typical terms at state and Transcarpathian region levels. Defining the indicators of crisis’ production component will provide an opportunity to analyze quantitative and qualitative characteristics of economic process. The crisis process indices’ nomenclature (indicators) is determined by the totality of the functional and structural crisis’ features, peculiarities and level of economic development, type of state governing, and time realia. The crisis process indices’ nomenclature is analyzed under the principles of system, hierarchy, relevance, uniqueness (as stimulants or disincentives of development) that allows to make regular and comprehensive monitoring of its values. The list of indicator or component sets is not sustainable, it can be supplemented and refined. The indicator of C-type is a stimulant, – that is there exists a direct relation between the stimulant and integral evaluation mark. The B-type indicator – is a disincentive, as there’s a reverse relation (opposite) between indicator-disincentive and feedback rate. The most common of indicators is a mixed A-type, which to a certain index rate is a stimulant, while in case of further increase becomes a disincentive part / subindex of economic security.
Features of the production component of the economic crisis at the state and regional level
Keywords: економічна криза; індикатори; порогове значення; характеристичні значення індикаторів; рівні економічної кризи; economic crisis; indicators; threshold account; characteristic values of indicators; economic crisis rates; 338.124